Fail-safe design of integral metallic aircraft structures reinforced by bonded crack retarders - Zhang, Xiang; Boscolo, Marco; Figueroa-Gordon, Douglas J.; Allegri, Giuliano; Irving, Phil E. (Elsevier, 2009)
This paper presents an investigation on the effectiveness of crack growth retarders bonded to integral metallic structures. The study was performed by both numerical modelling and experimental tests. It focuses on aluminium alloy panels reinforced by bonded straps made of carbon-epoxy, glass-epoxy composite materials or a titanium alloy. The goal was to develop a fail-safe design for integrally stiffened skin-stringer panels applicable to aircraft wing structures. The modelling strategy and finite element models are presented and discussed. The requirements that the models should meet are also discussed. The study has focused on establishing the extent of crack retarder benefits, in terms of fatigue crack growth life improvement, by numerical simulation and experimental tests of various crack retarders. The results of predicted fatigue crack growth retardation have been validated by tests of laboratory samples. This study concludes that by bonding discrete straps to an integral structure, the fatigue crack growth life can be significantly improved.
Keywords: Integral metallic structure; crack retarders; bonded straps; fail safe; fatigue crack